Resource mobilisation and allocation priorities on knowledge production in universities in Uganda: an empirical study - Eva Irene, Tumusiime (Kabale University Interdisciplinary Research Journal (KURJ), 2022)
Knowledge production is recognised as one of the core functions of a university, but its effective implementation has eluded many African universities, particularly those in Uganda. This paper analyses whether this situation is explained by these universities’ resource mobilisation and allocation priorities. Using a mixed research design, data was collected from purposively selected respondents and from interviews with top management officials of Universities. In addition, a structured questionnaire to faculty members who were conveniently selected from four of the largest universities in Uganda was used. Data was analysed using qualitative and quantitative methods of analysis. Results indicate that the selected universities’ resource mobilisation and allocation do not give knowledge production the priority it deserves. The priorities focus more on meeting the demands of the teaching, administrative and instructional infrastructure development functions. The research function is largely left out based on a view that it can generate its own resources not only through faculties and departments winning funded research projects and using university industry collaborations but also through research students and faculty members sponsoring their research projects. This view however, does not always hold. Consequently, the paper concludes by urging top management of Uganda’s universities that if they are to produce the knowledge expected of them, they have to give the research function the priority it deserves when mobilising and allocating resources.